Chromosomal Aberrations in Cattle - Holečková, Beáta; Schwarzbacherová, Viera; Galdíková, Martina; Koleničová, Simona; Halušková, Jana; Staničová, Jana; Verebová, Valéria; Jutková, Annamária (Genes, 2021)
Chromosomal aberrations and their mechanisms have been studied for many years in livestock. In cattle, chromosomal abnormalities are often associated with serious reproduction-related problems, such as infertility of carriers and early mortality of embryos. In the present work, we review the mechanisms and consequences of the most important bovine chromosomal aberrations: Robertsonian translocations and reciprocal translocations. We also discuss the application of bovine cell cultures in genotoxicity studies.
Keywords: genotoxic agents; skot; aberrations; chromozomální aberace; Cattle; Translocation, Genetic; cattle; Chromosome Aberrations; nemoci skotu; Robertsonian translocations; Animals; reciprocal translocations; translokace genetická; Cattle Diseases; chromosomes; zvířata